Impact Of Audit Factors On Audit Quality Of Investment Audits Funded By ODA - Ali Kadhim, Hussein Al-Fatlawi (Opción, 2019)
The purpose of the research is to analyze the determinant impact of the auditor’s factors on the performance auditing quality of ODA-funded investment project audits conducted by the State Audit Office of Vietnam (The SAV). Through the exploratory factor analysis (EFA) with the 204 state auditors surveyed by the Gen- eral Department, the State Audit of Region I and the Specialized State Audit IV, V. Notable results were found regarding five factors influencing the operational auditing quality of ODA-funded investment projects, namely: (1) technical compe- tence, (2): professional capacity; (3): experience of auditor; (4): professional atti- tude of the auditor and (5): ethical standard of the auditors. The results of multiple regression analysis show that the technical competence, professional capacity and professional attitude are the dominant factors affecting operational auditing quality of ODA-funded investment projects.